(untitled) (Global Journal of Science Frontier Research, 2020)
Cadmium (Cd) is a heavy metal with limited biological function, is widely distributed in the aquatic environment as a result of natural and anthropogenic activities. The effect of exposure on gilthead sea bream (Sparusaurata) fingerlings to sub-lethal concentrations of Cd was evaluated as levels of Cd content. The main objective of this study was to determine the effects of cadmium at sub-lethal concentrations (1 and 3 μg/L) on serum biochemical parameters including enzymes, i.e. alkaline phosphatase (ALP), aspartate amino transferase (AST) and alanine amino transferase (ALT), glucose, triglyceride, cholesterol and total protein in seabream (S. aurata) fingerlings, sea bream were exposed to cadmium at intervals of 1, 15, and 30 days, selected parameters were evaluated. Triglyceride and cholesterol decreased transiently at day 15 and then increased at day 30.Total protein, AST, ALT and ALP increased linearly by time and Cd concentration. This investigation suggests that growth and serum biochemical parameters could be used as important and sensitive biomarkers in ecotoxicological studies concerning the effects of metal contamination and fish health.